CORRUPTION AND TAX EVASION IN ROMANIA - MARIANA TRANDAFIR (Challenges of the Knowledge Society, 2011)
Tax evasion has become a ubiquitous phenomenon in economic and social. Extent it has taken a tax evasion is worrying because the lack of control measures may close in the future stability of national economy. To combat tax evasion is not necessary to impose some severe penalties, but should be made an effective fiscal control, a viable legal system.